Synthesis and swelling behaviour of hydrophobically modified responsive polymers in dilute aqueous solutions - Iyer, N. P.; Hourdet, Dominique; Badiger, Manohar V.; Chassenieux, Christophe; Perrin, P.; Wadgaonkar, P. (Polymer, 2005)
New series of associating polymers were synthesised in order to investigate opposite behaviours of hydrophobically modified water-soluble polymers and thermoresponsive water-soluble polymers carrying LCST stickers. On the basis of a poly(acrylic acid) backbone, amino-terminated poly(N-isopropylacrylamide), poly(ethylene oxide-co-propylene oxide) and/or dodecyl chains were grafted following a reaction of condensation activated by carbodiimide. Two homologous series of well-defined single grafted and double grafted copolymers were obtained, with double grafted chains containing both C12 and LCST grafts. The dilute solution properties of these copolymers were carefully studied by capillary viscometry. At low salt concentration and below the LCST of the grafts, the swelling properties of macromolecular chains are controlled either by intramolecular associations between hydrophobes, excluded volume effect exerted by hydrophilic grafts or by a balance between these opposite interactions. The deswelling of macromolecular chains, induced by hydrophobic interactions, is amplified at higher ionic strength and more particularly above the transition temperature of the side chains. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: associating polymers; poly(acrylic acid); viscometry

Structure and gelation mechanism of silk hydrogels - Nagarkar, Shailesh; Nicolai, Taco; Chassenieux, Christophe; Lele, Ashish K. (Physical Chemistry Chemical Physics, 2010)
Silk fibroin was regenerated from cocoons produced by the silkworm Bombyx Mori. Light scattering showed that an aqueous solution of the regenerated silk fibroin (RSF) was made of individual proteins with a weight average molar mass of about 4 x 10(5) g mol(-1) and a hydrodynamic radius of about 10 nm. Gel formation of RSF in acidic solutions was investigated as a function of the pH (2-4), concentration (0.5-10 g L(-1)) and temperature (5-70 degrees C). The structure of the gels was studied using light scattering and confocal laser scanning microscopy. The structure was found to be self-similar from length scales of less than 15 nm up to length scales of about 1 mm, and characterized by a correlation length of a few microns. Gel formation was tracked using turbidity, rheology, light scattering and circular dichroism. Gelation involves the formation of self-similar aggregates with a growth rate that increases exponentially. The protein aggregation is correlated to, and perhaps caused by, the formation of beta-sheets, the fraction of which also increases exponentially with time.